2007
DOI: 10.1038/ja.2007.69
|View full text |Cite
|
Sign up to set email alerts
|

Trierixin, a Novel Inhibitor of ER Stress-induced XBP1 Activation from Streptomyces sp.

Abstract: In the course of screening for an inhibitor of ER stress-induced XBP1 activation, we isolated a new member of the triene-ansamycin group compound, trierixin, from a culture broth of Streptomyces sp. AC 654. Trierixin was purified by column chromatography on silica gel and by HPLC. The molecular formula of trierixin is C 37 H 52 N 2 O 8 S. Trierixin inhibited thapsigargin-induced XBP1-luciferase activation in HeLa/XBP1-luc cells and endogenous XBP1 splicing in HeLa cells with an IC 50 of 14 ng/ml and 19 ng/ml, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…We have also reported that novel trieneansamycin group compounds, quinotrierixin and trierixin, inhibited ER stress-induced XBP1 mRNA splicing in HeLa cells. [15][16][17][18] In this study, we found that quinotrierixin inhibited protein synthesis. Moreover, we investigated the relationship between quinotrierixin-inhibited ER stress-induced XBP1 mRNA splicing and protein synthesis.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…We have also reported that novel trieneansamycin group compounds, quinotrierixin and trierixin, inhibited ER stress-induced XBP1 mRNA splicing in HeLa cells. [15][16][17][18] In this study, we found that quinotrierixin inhibited protein synthesis. Moreover, we investigated the relationship between quinotrierixin-inhibited ER stress-induced XBP1 mRNA splicing and protein synthesis.…”
mentioning
confidence: 75%
“…As reported previously, 15) HeLa cells were seeded in 12-well plates at 5 Â 10 4 cells/well, and then incubated with 10 mg/mL of tunicamycin with and without quinotrierixin and other protein synthesis inhibitors for 4 h. Subsequently, total RNA was extracted from the HeLa cells using TRIzol reagent (Invitrogen, Carlsbad, CA). Aliquots of 2.0 mg of the total RNA were treated with M-MLV reverse transcriptase (Promega, Madison, WI) to produce first-strand cDNA, which was subjected to polymerase chain reaction (PCR) with KOD plus polymerase (Toyobo, Osaka, Japan) using a pair of primers corresponding to nucleotides 505-524 and 609-629 of XBP1 cDNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…are known to secrete small molecules such as macrocytic lactams (e.g., trierixin), which directly inhibit XBP1 activation. 54 Similarly, Shiga toxigenic Escherichia coli secrete AB 5 cytotoxins that activate ER stress pathways by direct cleavage of grp78. 55 These and other examples show how there may be a bidirectional interaction between ER stress pathways within the epithelium and the microbial communities contained within the lumen, suggesting that different genotypes may converge phenotypically on ER stress pathways via effects on the intestinal microbiota.…”
Section: The Relationship Between Er Stress Pathways and Other Mechanmentioning
confidence: 99%
“…In this rapidly renewing tissue that is constantly exposed to noxious stimuli that may impact protein folding, Xbp1 may not only assist in resolving ER stress but may thereby keep the regenerative response, including stem cell activation, in check. However, overwhelming the remedial abilities of Xbp1 (e.g., through genetic hypofunction of Xbp1 or persistence of microbial or environmental ER stressors including those that inhibit Xbp1 function; Tashiro et al, 2007) may initiate a compensatory regenerative response, which is facilitative of neoplasias if persistent. In line with this, the architecture of ISCs in close proximity to Paneth cells is preserved in tumors , which we speculate might result in a situation in which the increase in ISCs and proliferative output in Xbp1 /(IEC) tumors may outcompete any potential survival disadvantage of differentiated epithelial cells caused by Xbp1 deficiency.…”
Section: Methodsmentioning
confidence: 99%